Opening Letter of RILEM TC SDM: The current situation of data and metadata management in construction materials research - Emerging demands and viable solutions - Tanja Manninger; Fabien Georget; Ravi Patel; Tulio Honorio; Gilberto Cidreira Keserle; Roman Wan-Wendner; Sandra Barbosa Nunes (RILEM Technical Letters)
To meet growing demands of stakeholders of the construction materials research field, new practices and methods must be established in handling metadata and raw data. Modelling approaches, simulation calculations and a targeted use of machine learning can save time and resources and is increasingly used in the industry as a decision-making tool. These techniques will play a crucial role in achieving the Net-Zero CO2 deadline of 2050. However, a better collaborative effort is required to ensure that data can be successfully reused. The task is challenging, as methods and strategies for data collection in the field of construction materials are diverse. The RILEM TC SDM (Scientific Metadata Management of Construction materials) aims to lay the foundation for a formal approach to metadata collection and management. As an initial step, a metadata collection framework and the associated input tool will be designed. Along with a best-practice guideline for the storage of raw data, this will help data producers establish a robust routine that aligns with the FAIR data principles, facilitating the data's reuse. The TC will provide the bridging element – the metadata file – that links the journal publication to the raw data. The metadata file can be easily stored and searched.